2019
DOI: 10.3390/ma12152486
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Methylene Blue Dye Using Natural Biosorbents Made from Weeds

Abstract: The purpose of this work is to make use of vegetables that, although widely found in nature, there are few applications. The weeds used here, Cyanthilium cinereum (L.) H. Rob (CCLHR) and Paspalum maritimum (PMT) found in the Amazon region of Belém state of Pará-Brazil, contribute to the problem of water contamination by the removal of the methylene blue dye through the biosorption process, taking advantage of other materials for economic viability and processing. The influences of parameters such as, biosorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 57 publications
1
25
0
2
Order By: Relevance
“…Dyes are used in many industries such as paper, plastics, photography, ink, and textile. While these industries use dyes to color their final products, it also results in imparting color to water and wastewater [1][2][3]. Methylene blue (MB) has found extensive use in the coloring of textiles [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyes are used in many industries such as paper, plastics, photography, ink, and textile. While these industries use dyes to color their final products, it also results in imparting color to water and wastewater [1][2][3]. Methylene blue (MB) has found extensive use in the coloring of textiles [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…is limitation has led to search for effective substitutes at a lower cost point. Among these, adsorption is a very effective and attractive technique with respect to cost, ease of use, and simplicity [1][2][3]. Several studies have reported the use of low-cost materials for dye removal [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of synthetic dyesin aquatic environments is the cause of color, whichis the first impact to recognize in an effeluent because very small amounts in water are very vesible. Dyes interfere also with the penetration of sunlights and thus delay photosynthesis, ibhibit the growth of aquatic biotics and interfere with the solubility of gases in water bodies [4]. Several organic dyes are hurmful to humans, methylene blue (MB) is not considered to be extremely toxic, but it can have various hurmful effects.…”
Section: Introductionmentioning
confidence: 99%
“…It can cause short period of fast or rapid breathing, while oral ingestion produces a burning sensation and can cause nausea, vomiting and diarrhea [5]. The most technique used for the removal for dyes are adsorption, precipitation, ion-exchange, membrane filtration, photocatalysis, flocculation and electrochemical treatment [4]. Among these methods, adsorption is preferred due to its simplicity, lower cost and high efficiency [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation